PENGARUH PEMBELAJARAN CASE STUDY DAN MIND MAPPING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SDN KEC. KOTO VII KAB. SIJUNJUNG: PENGARUH PEMBELAJARAN CASE STUDY DAN MIND MAPPING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SDN KEC. KOTO VII KAB. SIJUNJUNG - Mardiawati; Jamaris Jamna; Endang Wahyuningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Case Study and Mind Mapping learning models on the mathematical problem-solving ability of fourth-grade students at SDN Koto VII District, Sijunjung Regency. This research employed a quasi-experimental method with a non-equivalent control group design. The population consisted of all fourth-grade students, and the sample included two classes: the experimental class, which applied the Case Study and Mind Mapping models, and the control class, which used conventional learning methods. Data were collected through a descriptive test of mathematical problem-solving skills and analyzed using descriptive statistics and the independent t-test. The results revealed a significant difference between the learning outcomes of students taught using the Case Study and Mind Mapping models compared to those taught using conventional learning. The experimental class achieved a higher posttest mean score of 74, compared to 66 in the control class. These findings indicate that the implementation of Case Study and Mind Mapping learning models is effective in enhancing the mathematical problem-solving skills of elementary school students Keywords: Case Study, Mind Mapping, Problem Solving, Mathematics, Innovative Learning.